The effect of social media usage on employee job performance - UiTM, Faculty of Business and Management (UiTM, 2021)
Organizations currently performing in highly competitive environments are increasingly interested in adopting advanced technologies for their business operations. One of the places where technologies are widely used is social networking platforms, more commonly known as social media. Social media is not only used for entertainment and socialization but also used for business purposes in many organizations. However, knowledge about the impact of the use of social media on employee job performance is limited. Social media is all about awareness and connection, and presently social media seems to be a tool that affects the job performance of the employee in the workplace. The new media is growing so fast that it makes it imperative for employees to embrace the medium. The purpose of the study is to investigate the effects of social media usage on employee job performance.